PENGARUH GAYA HIDUP DAN MOTIVASI HEDONIS TERHADAP PEMBELIAN IMPULSIF PADA STARBUCKS COFFEE - Agus Salim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2017)
As the times progressed, drinking coffee was not just to get rid of sleep, but part of lifestyle. This happens because the increasingly busy urban communities that require a comfortable place to release fatigue. In addition, there is a hedonic motivation that makes people have the desire, self-existence and self-concept searching. So that lifestyle and hedonic motivation can create impulsive purchases of a product or service. Theories used to support this research are definitions, dimensions and indicators related to lifestyle variables, hedonic motivations and impulsive purchases. The research method used is descriptive method with survey approach and causal-predictive method. This study used questionnaires to collect data of 30 respondents for validity and reliability test. Then, as many as 100 respondents for the average test, scale range, multiple linear regression analysis and classical assumption test with non-probability sampling sampling technique with purposive sampling approach. This data is processed using SPSS 20.0 application. Output generated SPSS 20.0. shows that the value (Sig.) 0.001 <0.005 where lifestyle has a significant influence on impulsive purchase and hedonic motivation there is a value (Sig.) 0.018> 0.005 so no significant effect on impulsive purchases. The conclusions of this study indicate that there is sufficient evidence that lifestyle has a significant effect on impulsive purchases and there is not enough evidence that hedonic motivation has a significant effect on impulsive purchases.Â Keywords : Lifestyle, Hedonic Motivation and Impulsive Buying